Increased Hirsutella citriformis Conidia Shelf Life in Acacia and Hirsutella Gum Formulations - Rosa A. Flores-Villarreal; Alonso A. Orozco-Flores; Servando H. Cantú-Bernal; Ricardo Gomez-Flores; Orquídea Pérez-González; Patricia Tamez-Guerra (Applied Sciences, 2023)
Biological control by beneficial microorganisms is known to significantly reduce the effect of pests on crops yield. Among the biocontrol strategies is the use of entomopathogenic fungi such as Hirsutella citriformis, which has been applied to infect and kill hemipteran insect pests, including Diaphorina citri Kuwayama (Hemiptera: Liviidae) and Bactericera cockerelli Sulc. (Hemiptera: Triozidae). These biological agents are applied in the form of conidia that are often combined with other inert materials to facilitate application, protect conidia, and improve their shelf life. The aim of this study was to implement strategies for developing formulations to increase conidia shelf life. We evaluated gum produced from one strain and conidia from two different H. citriformis strains. Conidia were formulated by evaluating different concentrations of Acacia and Hirsutella gums to enhance conidia viability during storage at 4 °C or 25 °C. Results indicated that formulations maintained conidia viability for at least 90 d after storage at 25 °C (≥70% viability) and at least 120 d after storage at 4 °C, which was significantly (p ≤ 0.05) higher than that of the control, without observing changes in pH values. We also demonstrated 100% formulation purity from days 0 to 120, among all treatments. In conclusion, evaluated formulations maintained H. citriformis conidia viability for at least three months, when stored at 4 °C.